The external environmental policy of the European Union : EU and international law perspectives / edited by Elisa Morgera. - Morgera, Elisa (Cambridge University Press, 2012)
This collection of essays comprehensively and systematically analyzes the various instruments and innovative approaches through which the EU is forging its external environmental policy, the legal implications of its multifaceted practice and interactions with international environmental law. It explains the legal and institutional framework for EU external action on environmental protection and sustainable development, identifying the changes introduced, and challenges posed, by the Lisbon Treaty. It explores key tools and trends in defining and implementing EU external policy across a broad range of environmental issues, as well as linkages with trade and human rights. It also assesses the reciprocal influences between the development and implementation of EU environmental law and of international environmental law.